Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

Effects of nitrogen addition on soil faunal abundance: A global meta‐analysis - Junxi Hu; Shixing Zhou; Liehua Tie; Xiong Liu; Xing Liu; Anjiu Zhao; Jiaming Lai; Lin Xiao; Chengming You; Congde Huang (Global Ecology and Biogeography, 2022)
Aim Soil fauna has a wide range of ecosystem functions. Anthropogenic atmospheric nitrogen (N) deposition affects the structure and function of soil fauna by changing the microenvironment and resources. Given that soil faunal responses can vary considerably among taxonomic groups, N deposition rate, and ecosystems, however, there is little consensus. We aimed to evaluate the effects of N deposition on different soil faunal taxa across different terrestrial ecosystems. Location Global. Time period 1970–2021. Major taxa studied Soil fauna. Methods We conducted a meta‐analysis that yielded 264 observations from 43 publications. We evaluated the responses to N addition of soil faunal abundance for three different taxa (nematodes, mites, collembolans) in three ecosystem types (cropland, forest, and grassland). Results Our results showed an overall negative effect of N addition on soil fauna. However, the effect varied among soil faunal taxa. Specifically, N addition had no significant effects on the abundance of collembolans and mites in any ecosystem. On the other hand, N addition significantly reduced the abundance of all nematode trophic groups except bacterivores. The overall reduction of soil fauna is likely driven by the nematode response. The negative effects of N addition on nematode abundance were contingent on the N addition rate, N addition form, and ecosystem type. N addition decreased nematode abundance at N addition rates of more than 100 kg/ha/year. Inorganic N addition negatively affected nematode abundance. Finally, N addition had a greater adverse effect on nematodes in cropland and grassland compared to forest ecosystems. Main conclusions Our results demonstrate the overall negative effects of N addition on nematode abundance. Excessive N addition should be avoided in cropland and grassland management. Further, we suggest the application of organic fertilizer instead of inorganic fertilizer to minimize the N‐induced negative effects on soil nematodes.